Expression of tissue-specific imprinted gene tumor Suppressing Subtransferable Candidate 4 (TSSC4) is altered in placentae produced by nuclear transfer in cattle - Penteado, João C.T. [UNESP]; Borduchi, Rodolpho J. [UNESP]; Maldonado, Mariângela B.C. [UNESP]; Sangalli, Juliano R.; de Bem, Tiago H.C.; Meirelles, Flavio V.; Arnold, Daniel R.; Lopes, Flavia L. [UNESP] (Elsevier, 2017)
Embryonic and placental development is highly orchestrated by epigenetic processes. Disruptions in normal placental development, commonly observed in pregnancies produced by nuclear transfer, are associated with abnormal gene expression and altered epigenetic regulation of imprinted and vital placental genes. The objective of this study was to evaluate expression and epigenetic regulation of the imprinted gene TSSC4 in cotyledonary and intercotyledonary tissues from day 60 pregnancies produced by embryo transfer (ET), in vitro fertilization (IVF) and nuclear transfer (NT) in cattle. TSSC4 expression was reduced by 30% in cotyledons at 60 days of gestation in the NT group. The proximal promoter region of TSSC4 showed an increase in the permissive histone mark (H3K4me2) and a reduction in the inhibitory histone mark (H3K9me2) in the cotyledons produced by NT, in relation to cotyledons produced by embryo transfer. Interestingly, H3K9me2 was also significantly reduced in cotyledons produced by IVF, compared to the ET controls. DNA methylation, in CpG-rich regions located at the proximal promoter region and the coding region of TSSC4 did not differ. These results suggest that the reduction in TSSC4 expression, observed following NT, can not be explained by the histone changes investigated in the proximal promoter region of the gene, or by changes in methylation in three regions evaluated. Also, a decrease in the levels of H3K9 dimethylation in IVF samples, indicate that in vitro culturing could corroborate with the alterations seen in the NT group.
Keywords: Bovine; H3K4me2; H3K9me2; Placenta; TSSC4